Reliability and functional safety as the main components of the quality of passenger cars - S. V. Petrov; G. V. Raykov; Yu. V. Kornev; N. B. Karavanova (Вестник Научно-исследовательского института железнодорожного транспорта)
Quality of passenger cars is a complex property, depending on the reliability and functional safety of the cars. Therefore, guided by the standard definition of the term "quality", satisfaction of the parties concerned, in this case passengers, customer, carrier, infrastructure owner, supplier or state supervision bodies, can be achieved by meeting the requirements objectively established to the noted indicators. In order to establish the requirements for the reliability and functional safety of passenger cars, it is necessary to solve the following tasks: Selection of the nomenclature of indicators taking into account the peculiarities of using passenger cars for their intended purpose. Development of calculation methods and selection of parameters of test plans for reliability for the established nomenclature of indicators. Determination of the achieved level of reliability and safety of cars based on selected indicators. Establishment of standardized values of indicators taking into account achieved level on the basis of the principle of reasonable sufficiency. The article shows the nomenclature of the applied indicators of reliability and safety of passenger cars, as well as formulas for their calculation, accepted criteria for failures and limiting states of cars, requirements for the accuracy and reliability of the measured indicators. The work concludes that the establishment of requirements for indicators of reliability and functional safety of passenger cars allows taking into account the interests of all involved parties. For passengers, infrastructure owner and state supervision bodies, interests in the field of traffic safety will be taken into account; for the carrier - these requirements will be taken into account in terms of timely and safe transportation of passengers; for the customer - in terms of ensuring the good technical condition of the cars; for the manufacturer - in terms of preserving the reputation, ensuring the competitiveness of products, reducing costs to eliminate inconsistencies in its quality.